The Effect of FDI and GRDP on Industrial Labor Absorption in West Java - Misnahwati (Universitas Negeri Semarang, 2024)
This research aims to determine the effect of foreign direct investment FDI in the manufacturing industry subsector and gross regional domestic product (GRDP) on industrial labor absorption in West Java Province. The data analysis method used panel data regression using Fixed Effect Model (FEM) with the help of E-views 12 program. The results of this research show that partially, the FDI in the food and beverage industry has no effect on industrial employment absorption, FDI in the textile and textile product industry has a negative and significant effect on industrial employment absorption, and GRDP Industry has a positive and significant effect on industrial employment. Together, FDI in the food and beverage industry, textile and textile product industry, and industrial GRDP have a significant effect on industrial labor absorption.